Comprehensive in vitro pro‐arrhythmic assays demonstrate that omecamtiv mecarbil has low pro‐arrhythmic risk - Yusheng Qu; BaoXi Gao; Ziva Arimura; Mei Fang; Hugo M. Vargas (Wiley, 2021)
Abstract Omecamtiv mecarbil (OM) is a myosin activator (myotrope), developed as a potential therapeutic agent for heart failure with reduced ejection fraction. To characterize the potential pro‐arrhythmic risk of this novel sarcomere activator, we evaluated OM in a series of International Conference on Harmonization S7B core and follow‐up assays, including an in silico action potential (AP) model. OM was tested in: (i) hERG, Nav1.5 peak, and Cav1.2 channel assays; (ii) in silico computation in a human ventricular AP (hVAP) population model; (iii) AP recordings in canine cardiac Purkinje fibers (PF); and (iv) electrocardiography analysis in isolated rabbit hearts (IRHs). OM had low potency in the hERG (half‐maximal inhibitory concentration [IC50] = 125.5 µM) and Nav1.5 and Cav1.2 assays (IC50 > 300 µM). These potency values were used as inputs to investigate the occurrence of repolarization abnormalities (biomarkers of pro‐arrhythmia) in an hVAP model over a wide range of OM concentrations. The outcome of hVAP analysis indicated low pro‐arrhythmia risk at OM concentration up to 30 µM (100‐fold the effective free therapeutic plasma concentration). In the isolated canine PF assay, OM shortened AP duration (APD)60 and APD90 significantly from 3 to 30 µM. In perfused IRH, ventricular repolarization (corrected QT and corrected JT intervals) was decreased significantly at greater than or equal to 1 µM OM. In summary, the comprehensive proarrhythmic assessment in human and non‐rodent cardiac models provided data indicative that OM did not delay ventricular repolarization at therapeutic relevant concentrations, consistent with clinical findings.